Javanese Sufism: Ki Ageng Suryamentaram’s Gratitude Concept in the Book of Kawruh Jiwa - Mita Mahda Saputri (Journal of Sufism and Psychotherapy, 2021)
Gratitude in the teachings of Sufism is one of the stations that must be passed by humans to get closer to Allah SWT. Gratitude in Javanese, namely matur nuwun, akeh disawurake, diretaake, kasebar, and pating slebar. As gratitude in the book Kawruh Jiwa from Ki Ageng Suryomentaram, namely gratitude (nrimo) to Allah SWT for giving joys of happiness and warnings (calamities) that occur. The concept of gratitude in the Kawruh Jiwa book contains advice from Ki Ageng Suryomentaram especially about gratitude, adds discourse, insight, and understanding of the destiny of life experienced by humans. This is library research using qualitative methods. This study uses descriptive data in the form of words to find, develop, and test knowledge obtained through literature in the form of books, notes, and research reports from previous research as a source of data and facts to find answers for a problem. The results showed that gratitude to Allah SWT according to Ki Ageng Suryomentaram is a sense of nrimo which is carried out by understanding and studying the events that occur in life. Understanding and studying the destiny that occurs, what is seen is not the form of destiny or the gift, but from the Substance that gives that destiny. Thus it can be found the meaning or wisdom that occurs in life, to lead to a happy and peaceful life.